MANAGEMENT OF TIMIRA-KACHA-LINGANASA - Pratibha, *Upadhyay; Fiaz, Shamsa (International Journal of Ayurveda and Pharma Research, 2016)
The concept of Timira has been widely described in our ancient texts, in detail having its etiology, pathogenesis, treatment, even though the technology that we have today was not present in ancient period inspite of that there is exactly same description as we found in todays era. We will go through a short description of specific line of treatment of different stages of cataract as mentioned in our classical texts. Timira, Kacha and Linganasha are the successive stages of the same disease as mentioned in our ancient texts. Blurring of vision is described as Timira depending on its severity and Doshas, it is classified as subtypes, and when it is associated with raga it is termed as Kacha and if not treated in time it is converted to the incurable disease Lingnasha. Kaphaj lingnasha is considered to be cured through Shashtra karma. besides all preventive measures are also described in our texts regarding Timira.